Fast polarization mechanisms in the uniaxial tungsten-bronze relaxor strontium barium niobate SBN-81. Issue 1 (December 2017) - Buixaderas, E.; Kadlec, C.; Kempa, M.; Bovtun, V.; Savinov, M.; Bednyakov, P.; Hlinka, J.; Dec, J.
Abstract The high-frequency dielectric response of the uniaxial strontium barium niobate crystals with 81% of Sr has been studied from 1 kHz to 30 THz along the polarc axis by means of several techniques (far infrared, time domain terahertz, high-frequency and low-frequency dielectric spectroscopies) in a wide temperature interval 20–600 K. Relaxor properties were observed in the complex dielectric response and four main excitations were ascertained below the phonon frequencies. These fast polarization mechanisms take place at THz, GHz and MHz ranges and show different temperature evolution. The central mode excitation in the THz range, related to anharmonic dynamics of cations, slightly softens from high temperatures and then hardens belowT 400 K. Below the phase transition (atT 330 K) an additional microwave excitation appears near 10 GHz related to micro domain wall oscillations. The strongest relaxation appears in the GHz range and slows down on cooling according to the Arrhenius law. Finally, another relaxation, present in the MHz range at high temperatures, also slows down on cooling at least to the kHz range. These two relaxations are due to polar fluctuations and nanodomains dynamics. Altogether, the four excitations explain the dielectric permittivity maximum in the kHz range.